2022
DOI: 10.3390/medicina58070914
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Contact Cell-Mediated Hypersensitivity in Psoriasis: A Narrative Minireview

Abstract: The dysfunctionality of the protective skin barrier in psoriasis allows easier cutaneous penetration of various contact haptens; thus, such patients can develop allergic contact hypersensitivity as a comorbidity. Both skin conditions involve T-cell-mediated mechanisms. Dermatologists and allergists should consider assessing allergic contact cell-mediated hypersensitivity in selected psoriasis patients, especially those with palmoplantar psoriasis and who are refractory to topical treatments, and in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 77 publications
(129 reference statements)
1
5
0
Order By: Relevance
“… 14 Histological assessments of psoriasis samples reveal epidermal hyperplasia with elongated rete ridges, parakeratosis associated with focal orthokeratosis, and the presence of neutrophil (Munro) abscesses, as well as a disappearance of the granular layer of the epidermis and T-cell infiltrate. 1 These findings align with the results of in vivo and in vitro experiments, which show that keratinocytes in psoriasis patients are less susceptible to apoptosis. 15 , 16 On the other hand, ACD is a type IVa hypersensitivity reaction, characterized by 2 distinct phases.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“… 14 Histological assessments of psoriasis samples reveal epidermal hyperplasia with elongated rete ridges, parakeratosis associated with focal orthokeratosis, and the presence of neutrophil (Munro) abscesses, as well as a disappearance of the granular layer of the epidermis and T-cell infiltrate. 1 These findings align with the results of in vivo and in vitro experiments, which show that keratinocytes in psoriasis patients are less susceptible to apoptosis. 15 , 16 On the other hand, ACD is a type IVa hypersensitivity reaction, characterized by 2 distinct phases.…”
Section: Discussionsupporting
confidence: 84%
“…On one hand, the coexistence of contact sensitization with psoriasis may explain the localization of some lesions, treatment resistance and prognosis with increased skin disease morbidity. 1 Jo et al reported a case of Koebner phenomenon due to allergic contact hypersensitivity and suggested investigating for possible contact sensitization if the pruritic lesions involve pustules and vesicles. 8 However, several epidemiological and cohort studies have reported an inverse relationship between the 2 diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations